PENGARUH EKSTRAK KULIT BATANG ANGSANA (Pterocarpus indicus W.) TERHADAP JUMLAH SPERMA EJAKULAT MENCIT (Mus musculus L. Swiss Webster) - Suharti, Asmi - (STKIP PGRI Sumbar, 2014)
This study aimed to determine the effects of Angsana (Pterocarpus indicus W.) bark extract on sum mice sperm. This experiment used completelly randomized design with 3 treatment and 9 replications. The treatments were : 0 gr/kgbw (P1), 0,1 gr/kgbw (P2), 0,2 gr/kgbw (P3) âangsanaâ bark extract given ones dayly during 36 days. The parameter of this research were sum sperm of quality, of sperm including normal and abnormal sperm. After mice diceplication, researction, the vas deferens was ceparatic and presured. Sum of sperm and the quality of sperm was determine by improved neubauer and eosin stained. The data analisys ANOVA an followed by DMNRT. The result showed angsana bark extract not effect. The sum of sperm ajaculated but it effect to sperm quality including normal and abnormal sperm of the mice.